2016
DOI: 10.1038/tp.2015.217
|View full text |Cite
|
Sign up to set email alerts
|

Short environmental enrichment in adulthood reverses anxiety and basolateral amygdala hypertrophy induced by maternal separation

Abstract: Maternal separation during early childhood results in greater sensitivity to stressors later in adult life. This is reflected as greater propensity to develop stress-related disorders in humans and animal models, including anxiety and depression. Environmental enrichment (EE) reverses some of the damaging effects of maternal separation in rodent models when provided during peripubescent life, temporally proximal to the separation. It is presently unknown if EE provided outside this critical window can still re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
80
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(89 citation statements)
references
References 57 publications
7
80
1
1
Order By: Relevance
“…In our experiment, the potentiated corticosterone increase of MS/SH rats in response to an acute stressor (i.e., cage rotation) was not associated with elevated basal corticosterone in MS/SH compared to NMS/SH groups. This finding is in accordance with studies reporting no differences in basal concentrations in animals previously exposed to early‐life stress (Knuth and Etgen, 2007; Koe et al, 2016; Rüedi‐Bettschen et al, 2005; Slotten et al, 2006; Wigger and Neumann, 1999). Given the significant role of the hippocampus, particularly its glucocorticoid receptor (GR) system, in the HPA negative feedback mechanism, it may be suggested that hippocampal alterations may be associated with the potentiated stress response.…”
Section: Discussionsupporting
confidence: 93%
“…In our experiment, the potentiated corticosterone increase of MS/SH rats in response to an acute stressor (i.e., cage rotation) was not associated with elevated basal corticosterone in MS/SH compared to NMS/SH groups. This finding is in accordance with studies reporting no differences in basal concentrations in animals previously exposed to early‐life stress (Knuth and Etgen, 2007; Koe et al, 2016; Rüedi‐Bettschen et al, 2005; Slotten et al, 2006; Wigger and Neumann, 1999). Given the significant role of the hippocampus, particularly its glucocorticoid receptor (GR) system, in the HPA negative feedback mechanism, it may be suggested that hippocampal alterations may be associated with the potentiated stress response.…”
Section: Discussionsupporting
confidence: 93%
“…The LH paradigm used in this study consisted of the following conditions: 1) an escapable shock (ES) subject and 2) a no shock or “naïve to aversive stimuli” group (NS), where these animals were exposed to, but did not directly experience shock on the first day. Each LH condition assesses different aspects of depressive-like behavior via separate neuronal circuitry [28, 36]. Our previous studies found that females exposed to MS exhibited increased escape latency in the NS group only [26], an LH condition associated with motivational circuitry [26, 40, 41].…”
Section: Methodsmentioning
confidence: 99%
“…MS is associated with changes in GABA in the prefrontal cortex (PFC [22-24]) and the amygdala [25]. Rats with a history of MS show changes in PFC-mediated behaviors including learned helplessness (LH), working memory deficits, depressive-like behavior, and reduced social interaction [24, 26-28]. Prior studies show reduced GABAergic calcium-binding protein parvalbumin (PVB) expression in MS adolescent males [24] and females [26] and the basolateral amygdale in MS (BLA; [22, 23]).…”
Section: Introductionmentioning
confidence: 99%
“…Next, to examine if positive life experiences may result in opposing patterns of H3.3 dynamics in NAc, we used an EE paradigm that has previously been shown to promote enhanced synaptic plasticity and cognition and can prevent or reverse some aspects of depressive-like behaviors, such as anhedonia and anxiety (16)(17)(18). We observed that EE results in a significant down-regulation of H3f3b, but not of H3f3a, expression in mouse NAc (Fig.…”
mentioning
confidence: 90%